Bishop Gabriel (Kikodze) of Imereti - defender of the Georgian language - Tkeshelashvili, Levan (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2023)
In the early 19th century, the Georgian principalities were forcibly incorporated into the Russian Empire. The Russian government attempted to eradicate the Georgian language from educational settings and replace it with Russian. Bishop Gabriel Kikodze of Imereti (1860-1896) made a significant contribution to the preservation of the Georgian language. Gabriel, an uncompromising figure, confronted high-ranking Russian officials and even the Exarch of Georgia, presenting factual arguments for the importance and necessity of Georgians learning their native language, while acknowledging the value of also learning Russian alongside Georgian. In his letters, Bishop Gabriel openly criticized the Russian authorities for stripping the clergy in Georgia of their sacred right to educate people in the Orthodox faith. Under Russian rule, parish schools shifted focus from religious education to the study of the Russian language, depriving students of religious instruction and exacerbating societal issues. Bishop Gabriel›s correspondence is intriguing from multiple perspectives; it elucidates the threats faced by the Georgian clergy under Russian rule, critiques Russian educational policies that caused unrest among the Georgian populace, and defends the integrity of the Georgian language“. This version aims to clarify and enhance the original text for better readability and accuracy.